Mountains and valleys - Parker, Steve (San Diego, California : Thunde Bay Press, 1996)
Looks at how the highest and lowest places on Earth are formed, and discusses climate zones and weather factors for mountains and valleys.
Keywords: Mountains -- Juvenile literature; Valleys -- Juvenile literature